Young Learnes Vocabulary Understanding at Great Kids English Course in Duri - Musfiroh, Musfiroh (LPPM STMIK Dharmapala Riau, 2024)
Early childhood education is one of the determining factors in taking education to the next level. At this time, children begin to receive education, namely the beginning of academic skills such as reading, writing and arithmetic. One of the children's academic knowledge both at school and in society is language skills, both Indonesian as the national language and regional languages ​​as well as foreign languages ​​such as English. Even though English has been taught since elementary school, there are still some of us who cannot communicate well in this language. Even though English is not the mother tongue, it has become the language of international communication. That's why I chose this method to master English vocabulary using cards. This method is an effective learning method for early childhood, because with the help of picture objects, they can easily understand and remember English vocabulary. An effective way to use flash cards is to improve the listening, writing, memorizing and pronunciation skills included in the training or course. This stage is a test (pre-test) for early childhood at the beginning of learning, which measures mastery or knowledge of English vocabulary. Meanwhile, an assessment (post-test) is carried out at the end of each session to measure the child's ability and absorption.